Regenerative strategies for intervertebral disc degeneration - Raed H. Ogaili; Ahmed Alassal; Nurul Fariha Za'aba; Izzat Zulkiflee; Isma Liza Mohd Isa (Journal of Orthopaedic Translation, 2025)
Low back pain (LBP) is a global health problem, primarily caused by intervertebral disc (IVD) degeneration. Current treatments focus on symptom relief without addressing the underlying degenerative mechanisms. Regenerative strategies have emerged as promising therapies through the use of functional biomaterials and stem cells capable of modulating key signalling pathways to promote tissue regeneration. However, challenges such as efficient delivery systems, long-term survival of transplanted cells, and hostile disc microenvironment remain. This review focuses on recent advances in regenerative approaches using biomaterials, cells, and therapeutic agents of exosomes, and genes to restore IVD structure and function. We discuss the current understanding of IVD anatomy, physiology and degeneration pathophysiology followed by current treatments. We highlight the rationale for regenerative therapy in halting the degenerative hallmarks tailored to mild, moderate to severe IVD degeneration. Our review emphasizes on the functional biomaterials designed for advanced delivery system, therapeutic intervention and IVD tissue engineering. We discuss the cell-based therapy, highlighting various cell sources, therapeutic effects, clinical trials and its obstacles. We discuss the use of therapeutic agents such as the genes and exosome therapies in IVD regeneration. The clinical translational potential of regenerative therapy is vast and promising, driven by advances in cellular therapies, biomaterials, and cell-free approaches like exosomes, which offer new avenues for regenerating degenerative IVDs. While significant progress has been made in developing safe, effective, and scalable treatments, challenges remain in immune compatibility, manufacturing, and regulatory pathways. Emerging innovations in gene editing, 3D bioprinting, and personalized approaches are poised to accelerate the translation of these therapies into mainstream medicine, with interdisciplinary collaboration and global efforts playing a crucial role in overcoming current bottlenecks and realizing the full potential of regenerative medicine to transform patient care. This article offers a comprehensive framework to guide preclinical research and future clinical translation of effective regenerative therapies, aiming at reducing the global burden of LBP and improving long-term patient outcomes.